INTERACTIVE AI FOR MORE EFFECTIVE HUMAN RESOURCE MANAGEMENT - Mohanad hussein hamood alsaraji (Scholar Express Journals, 2022)
Organizations are growing and increasingly in need of analytics and artificial intelligence, to help improve irresistible business functions. Has this trend achieved itself in the field of human resources (HR), and what do I mean in the context of human resource management? Is there a scenario where the entire HR function will profit into bots? While the widely used “people analytics” in HR is related to data collection on employees and measurement metrics, AI can be described as machine learning where applications have the ability to learn from decisions based on data collected, made, or recommendation out; Using media articles and academic journals .
Keywords: Artificial Intelligence; Human Resources; Organizations